Implementasi Metode Jibril dalam Pembelajaran Al-Qur’an dan Penguatan Nilai Islam pada Ekstrakurikuler Tahfiz - Alvi Nurdiana; Amirul Huda AlMuflih; Isyadi Isyadi; Abdu Ghani Asrori; Lukmanul Hakim; Muqtadir Muqtadir; Ahmad Abdul Aziz (IIQ An Nur Yogyakarta, 2026)
This study analyzes the implementation of the Jibril Method in Qur’an reading instruction and its contribution to strengthening Islamic values in the ta?f?? extracurricular program at MTs Nurul Huda Sambisari, Surabaya. A descriptive qualitative design was employed. Data were collected through classroom observation, semi-structured interviews with the head of the madrasah, the ta?f?? instructor, and four students, as well as program documentation. The data were analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing and verification. Trustworthiness was established through source, technique, and time triangulation, member checking, and referential adequacy. The findings indicate that the Jibril Method was implemented through three integrated stages: planning based on students’ initial ability and semester targets; instruction through talq?n, taql?d, talaqq?, musy?fahah, collective-individual repetition, and immediate corrective feedback; and formative evaluation through reading assessment, tasm?‘, mur?ja‘ah, progress records, and individualized follow-up. The method improved pronunciation, tajw?d application, fluency, and tart?l reading while simultaneously strengthening religiosity, discipline, responsibility, patience, respect for teachers, consistency, and love of the Qur’an. These values developed through teacher modeling, repeated habituation, dialogical correction, and accountability for learning targets. Teacher competence, institutional and parental support, student motivation, and adequate facilities supported implementation, whereas limited time, heterogeneous initial ability, and inconsistent home practice constrained it. The study concludes that the Jibril Method functions as a dual pedagogical approach: it enhances the technical quality of Qur’an reading and facilitates the internalization of Islamic character.